2015
DOI: 10.1108/ijshe-08-2013-0106
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in sustainability education

Abstract: Purpose -This paper aims to examine how both the amount and type of coursework impact students' conceptualizations of sustainability. Previous research demonstrates that academic coursework influences students' environmental attitudes, yet few studies have examined the impact of coursework on how students conceptualize "sustainability". Design/methodology/approach -Data are examined from the 2011 Sustainability Survey, which yielded a sample of 552 students at a medium-sized university in the southeastern USA.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
41
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(53 citation statements)
references
References 41 publications
(43 reference statements)
4
41
0
1
Order By: Relevance
“…This is in line with Fisher and McAdams's conclusions that the number of sustainability courses in study programs has less impact on students' perceptions of sustainability than integrating sustainability themes in disciplinary classes [22]. However, Warburton highlighted that the interconnectedness of environmental, social, and economic issues in sustainability and deep learning (finding the underlying meaning to form a coherent whole of information) can be lost if the students have a strong disciplinary background and focus in their studies [36].…”
Section: Student Learning Of Sustainability In Educationsupporting
confidence: 72%
See 1 more Smart Citation
“…This is in line with Fisher and McAdams's conclusions that the number of sustainability courses in study programs has less impact on students' perceptions of sustainability than integrating sustainability themes in disciplinary classes [22]. However, Warburton highlighted that the interconnectedness of environmental, social, and economic issues in sustainability and deep learning (finding the underlying meaning to form a coherent whole of information) can be lost if the students have a strong disciplinary background and focus in their studies [36].…”
Section: Student Learning Of Sustainability In Educationsupporting
confidence: 72%
“…Hicks [14] indicated that learning about global issues such as sustainability and acting upon it can never be solely a cognitive matter, but must also involve an affective understanding. Nonetheless, increasing knowledge may not automatically result in changes in awareness and actions [15], so educational institutions aim at development of deeper circular learning patterns, where the knowledge is reflected upon and questioned in learning loops before application [12,[16][17][18] Several studies have focused on students' perceptions of sustainability [19][20][21], the impact of the amount and type of coursework on students' conceptualizations of sustainability [22], and the relationships of demographic factors on students' environmental awareness, knowledge and behavior [23,24]. However, limited studies exist on the results of sustainability implementation in education, as was highlighted by Tilbury [25], and on students' learning progress about sustainability during their university studies, according to McKeown [26].…”
Section: Introductionmentioning
confidence: 99%
“…Institutions of higher education play a fundamental role in addressing environmental sustainability. As the term “sustainability” gains traction within a diversity of campus programs and operations, it is important to understand the broader aspects of sustainability—environmental; community; innovation; and design and systems (Fisher and McAdams 2015). Additionally, the integration of sustainability into course programming, which requires new approaches to teaching and learning, has to be emphasized (Everett and Rowe 2008).…”
Section: Underrepresentation In the Stem Fieldsmentioning
confidence: 99%
“…Additionally, the integration of sustainability into course programming, which requires new approaches to teaching and learning, has to be emphasized (Everett and Rowe 2008). Research has shown that sustainability programs should incorporate learning that exposes students to various sustainability approaches early on and be presented in a way in which disciplinary focus is situated within a larger context (Fisher and McAdams 2015). However, this integration is slow and quite varied across institutions, and calls into question what is actually being learned and the quality of that learning (Remington-Doucette et al 2013).…”
Section: Underrepresentation In the Stem Fieldsmentioning
confidence: 99%
“…One study of a university in the southeastern USA (n = 552) found that students exposed to sustainability content in a course are aware of it but lack a well-rounded and holistic understanding of the topic [25]. The Higher Education Academy of the UK published a report in 2015 about students' attitudes and skills for sustainable development (n > 5000); when students were asked to describe sustainable development, "the environmental dimension also continues to be more prominent…" [26].…”
Section: Introductionmentioning
confidence: 99%